1980
DOI: 10.1007/bf00046800
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grazing on the quantity and quality of freshwater Aufwuchs

Abstract: Qualitative and quantitative measures of the Aufwuchs (scum flora) on artificial substrates in situ were used to evaluate the effects of grazing by freshwater pulmonate snails in a shallow pond in southeastern Michigan . Grazer densities of-216 snails/ M 2 marked reduced standing crop so that after 45 days grazed substrata had 6 .46 mg dry weight, 604 µg C and 4.18 µg chlorophyll a as compared to controls with 30 .62 mg dry weight, 3699 µg C and 6 .29 µg chlorophyll a, all on a per dm 2 basis .Grazing did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
59
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(70 citation statements)
references
References 37 publications
(53 reference statements)
11
59
0
Order By: Relevance
“…The present results confirm that freshwater pulmonate snails are generalist feeders grazing on epiphytic algae, decaying macrophytes and fine detritus as has been demonstrated for several species belonging to the Lymnaeidae, Physidae and Planorbidae (Pimental & White, 1959;Gohar & El-Gindy, 1961;Hunter, 1961;Malek, 1958;Clampitt, 1970a, b;Storey, 1971;Reavell, 1980;Hunter, 1980). No fresh fragments of aquatic macrophytes were found in the present studies and animal remains were found only on a few occasions.…”
Section: Discussionsupporting
confidence: 70%
“…The present results confirm that freshwater pulmonate snails are generalist feeders grazing on epiphytic algae, decaying macrophytes and fine detritus as has been demonstrated for several species belonging to the Lymnaeidae, Physidae and Planorbidae (Pimental & White, 1959;Gohar & El-Gindy, 1961;Hunter, 1961;Malek, 1958;Clampitt, 1970a, b;Storey, 1971;Reavell, 1980;Hunter, 1980). No fresh fragments of aquatic macrophytes were found in the present studies and animal remains were found only on a few occasions.…”
Section: Discussionsupporting
confidence: 70%
“…A comparatively large number of investigations have shown that, in freshwater habitats, grazers can control microalgal biomass, affect productivity and species richness, and change the composition of the biofilm (e.g. Hargrave 1970, Cooper 1973, Hunter 1980, Lowe & Hunter 1988, Swamikannu & Hoagland 1989, McCormick & Stevenson 1991, Rosemond et al 1993). In contrast, marine studies have in the past focused primarily on the effects of grazers on microalgal biomass and composition (Castenholz 1961, Nicotri 1977, Hunter & Russell-Hunter 1983, Mak & Williams 1999, Williams et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…However, lymnaeid snails rely on the aquatic environment for food, and L. columella frequently returns to the water to forage. Their feeding behavior is similar to that of the physid snails, which have a huge impact on plant and macrophyte communities (Hunter 1980) and exhibit significantly greater Patterns of Echinostoma spp. infections in snails 507 vagility than Helisoma spp.…”
Section: Discussionmentioning
confidence: 95%
“…employ a basic system of 'give up time' in which they continually change patches when resources become depleted (Charnov et al 1976, Dillon 2000 Lymnaeid snails, similar to the other pulmonates, show a dietary preference for algae (Bovbjerg 1965, 1968, Hunter 1980, Reavell 1980. These snails typically possess sand in their stomachs, which they use to aid in the digestion of more complex food items such as algae and live plant tissue (Storey 1970, Reavell 1980.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation